2014
DOI: 10.1111/tpj.12594
|View full text |Cite
|
Sign up to set email alerts
|

Precise spatio‐temporal modulation of ACC synthase by MPK6 cascade mediates the response of rose flowers to rehydration

Abstract: These authors contributed equally to this work. SUMMARYDrought is a major abiotic stress that affects the development and growth of most plants, and limits crop yield worldwide. Although the response of plants to drought has been well documented, much less is known about how plants respond to the water recovery process, namely rehydration. Here, we describe the spatio-temporal response of plant reproductive organs to rehydration using rose flowers as an experimental system. We found that rehydration triggered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…Further research on rose flowers showed that, particularly in the gynoecia, protein levels of RhMPK6 are high during both dehydration and rehydration, but RhMPK6 kinase activity was observed only within the first hour of rehydration. Active RhMPK6 is able to phosphorylate and stabilize RhACS1, stimulating ET production ( Meng et al, 2014 ). The RhMPK6-RhACS1 module seems to be crucial for transduction of the rehydration signal and triggering of ET biosynthesis, which controls flower opening and senescence in rose.…”
Section: Mapk Kinase Cascades In Ethylene Biosynthesis and Signalingmentioning
confidence: 99%
“…Further research on rose flowers showed that, particularly in the gynoecia, protein levels of RhMPK6 are high during both dehydration and rehydration, but RhMPK6 kinase activity was observed only within the first hour of rehydration. Active RhMPK6 is able to phosphorylate and stabilize RhACS1, stimulating ET production ( Meng et al, 2014 ). The RhMPK6-RhACS1 module seems to be crucial for transduction of the rehydration signal and triggering of ET biosynthesis, which controls flower opening and senescence in rose.…”
Section: Mapk Kinase Cascades In Ethylene Biosynthesis and Signalingmentioning
confidence: 99%
“…The transcriptional and post-translational regulation of ethylene synthesis proved pivotal for plant development and ripening [ 34 , 52 54 ]. Previous studies demonstrated that wound- and ABA-induced ethylene synthesis mostly depended on post-transcriptional regulation [ 7 , 38 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…During dehydration and rehydration, the protein level of a specific MAP kinase, RhMPK6, was maintained at a constant high level. However, RhMPK6 activity was only detected within 1 h of rehydration [ 16 ]. Furthermore, activated RhMPK6 phosphorylated and stabilised RhACS1, a rate-limiting enzyme of ethylene biosynthesis, and resulted in an ethylene burst in gynoecia.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that a MAPKK protein, RhMKK9, could phosphorylate the RhMPK6 protein in vitro [ 16 ]. However, to date it is unknown whether RhMKK9 is the actual upstream component activating RhMPK6 in gynoecia during rehydration.…”
Section: Introductionmentioning
confidence: 99%